Assessment of gastrointestinal symptoms in neurologically impaired children with PEG using peptide versus casein based formulae - Sara Tarek; Ayman E. Eskander; Alaa Mohamed Younis; Christine G. Salama; Walaa ElNaggar (SpringerOpen, 2024)
Abstract Background Nutritional interventions are a key strategy for sustaining general health in children with neurological impairment. Whey-based formulae have been shown to reduce gastroesophageal reflux and accelerate gastric emptying. Casein protein, on the other hand, precipitates in the stomach's acidic environment, slowing down gastric emptying. Methods This is a prospective observational study that included 34 children with severe neurological impairment between 2-14 years old of both sexes who underwent percutaneous endoscopic gastrostomy (P.E.G) tube insertion, gastrointestinal dysfunction symptoms and nutritional status were compared after 6 months between those fed either peptide-based (100% whey) or casein-based formula. We aimed in the current study to determine whether peptide-based formula reduces gastroesophageal reflux episodes and improves symptoms of poor feeding tolerance compared to casein-based formula, and to evaluate the impact of both formulae on the nutritional status of those children. Results Using peptide-based, 100% whey protein formula was associated with improved feeding tolerance and reduced gastrointestinal issues such as constipation (p-value = 0.016), reflux, and vomiting episodes (p-value = 0.034). Unlike patients who obtained the casein-based formula, patients who received the peptide-based formula exhibited significant improvement in swallowing ability 6 months after PEG insertion when compared to pre-insertion (p-value = 0.002). Conclusion Whey-based formula is better recommended for neurologically impaired children who have poor swallowing abilities, constipation, reflux, and vomiting episodes.